Operation characteristic of Integrated Pressurized Water Reactor under coordination control scheme. (January 2015) - Du, Xue; Xia, Genglei; He, Lihui
Highlights: Operating characteristic of IPWR under coordination control scheme was studied. The research model of IPWR is established using RELAP5 code. The ideal steady-state control system adjusts reactor power following steam flow. OTSG grouping run can improve the operating characteristics of OTSG. Abstract: Once-Through Steam Generator (OTSG) with smaller size and larger heat transfer capability, is typically used for Small and Medium sized Reactors (SMRs). Because the Integrated Pressurized Water Reactor (IPWR) uses OTSG, the feed water is heated to superheated steam by primary coolant, and the higher steam temperature could improve the thermal efficiency of the reactor power plant. However, the smaller size and heat capacity make stable operation more difficult. In this paper, a mathematical model of IPWR is established using RELAP5 code, and a coordination control scheme is used to study the rapid load following characteristics of OTSG. The effects of main operating parameters related to stable operation of OTSG are investigated. Average coolant temperature, steam pressure and OTSG grouping run operation boundary are confirmed. This operation boundary can be used to design and optimize the control system.